The Mediating Effects of Government Innovation Capabilities and ICT Development: E-Government Implementation and Organizational Value Creation in Indonesia - Lili Khamiliyah; Agus Rahayu; Maya Sari; Puspo Dewi Dirgantari (Dinasti Publisher, 2025)
Various studies provide evidence that E-Government Implementation contributes to Organizational Value Creation, but more research is still needed to analyze the mediation effect of Government Innovation Capabilities and ICT Development in the influence of E-Government on Organizational Value Creation in Indonesia. Using primary research data sourced from primary data, questionnaires were distributed to respondents with a total sample of 268, answering the formulation of hypotheses and research models using a parallel mediation effect approach, namely using SEM-PLS and SPSS V.3.4, The results of the study indicate that there is a direct effect of E-Government on Organizational Value Creation, as well as an indirect effect of E-Government on Organizational Value Creation through Government Innovation Capabilities and ICT Development; the influence is more apparent if, through ICT Development, this is possible because of the uneven development and implementation of ICT due to the level of accessibility, use, and skills. In addition, efforts that can be made to improve organizational innovation capabilities must involve essential elements, namely, Top Management, Adequate resources and Absorptive capacity, Organizational slack, Cross-functional collaboration, and Organizational challenges. Researchers suggest that local governments in Indonesia strengthen institutions, technology-based services, and governments that could innovate in providing services to the community to increase good, reliable, effective, efficient, and adaptive organizational governance to changes and community needs.